Teaching Materials Design for Muhadatsah Lesson for 7th Grade Students Muhammadiyah Boarding School Yogyakarta - Fairuz Subakir Ahmad; Abdul Hafidz bin Zaid; Tsaniya Ruchamainnisaa (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Muhammadiyah Boarding School (MBS) Yogyakarta paid great attention to teaching Arabic with the four elements of language skills, especially speaking skills (muhadatsah). Seeing the importance of these skills, MBS held language activities to support the students’ speaking skills, including muhadatsah activities. However, in its implementation, there is no specific teaching material for this muhadatsah activity. For this reason, researchers are trying to compile class VII special muhadatsah teaching materials based on research in the Muhammadiyah Boarding School field. This research is a Research Development (RD) type of research. In collecting data, researchers used the method of interviews, questionnaires, tests, and documentation. The main results of this study include, the muhadatsah teaching material is a book in which there is a collection of hiwar texts about the daily life of students equipped with vocabulary often used in Arabic conversations and practice exercises. The presentation of this material is also equipped with attractive colors and images. The students' test scores shows that this teaching material is effective for use in teaching muhadatsah. This result is seen from the analysis of the value of the students which shows that there are differences in values before using this teaching material and after using the teaching material that has been prepared for muhadatsah learning.